CampesinaCulture: a focus on the denial of the identity of the field in the Art teaching book - Jaklane de Abreu Santos; Sara Ingrid Borba (Universidade Estadual de Alagoas, 2021)
This work aims to analyze the focus on the denial of peasant culture in an Art textbook, as well as the impossibilities that this material presents for the identity construction of the student in the field. The didactic composition of the material was analyzed: contents, texts, images, where the theoretical aspects of Caldart (2011), Saviani (2007), Arroyo (2011), Hall (2004), Araújo (2016) and others were taken into account essential sources. The construction of the work took place through theoretical study, document analysis and participatory research, with a qualitative basis, resulting in the understanding that the document analyzed does not bring approaches that allow the identity construction of the student in the field.